1997
DOI: 10.1002/(sici)1097-0215(19970529)71:5<796::aid-ijc17>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutations in relation to human papillomavirus type 16 infection in squamous cell carcinomas of the head and neck

Abstract: The relationship between human papillomavirus (HPV) type 16 infection and p53 gene mutations was investigated in squamous cell carcinomas of the head and neck (SCCHN). HPV was detected by general primer-mediated and typespecific PCR. Alterations in the p53 gene were investigated using single-strand conformation polymorphism and sequence analysis in 27 SCCHN, of which 12 were HPV 16-positive and 15 were HPV-negative. Mutations The p53 tumour-suppressor gene (TSG) plays an important role in cellular responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
(22 reference statements)
1
19
1
1
Order By: Relevance
“…As expected by the high prevalence of HPV in our patient group, no correlation was established between viral presence and other clinicopathologic characteristics (age, gender, and cancer differentiation). Such associations have been reported by some groups (13,15,38) but could not be confirmed by others (34,43,59). In addition, anatomic site seems to be an important factor that determines the susceptibility of squamous epithelium to HPV transformation, with the tonsillar region being more sensitive (13,15,22,35).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As expected by the high prevalence of HPV in our patient group, no correlation was established between viral presence and other clinicopathologic characteristics (age, gender, and cancer differentiation). Such associations have been reported by some groups (13,15,38) but could not be confirmed by others (34,43,59). In addition, anatomic site seems to be an important factor that determines the susceptibility of squamous epithelium to HPV transformation, with the tonsillar region being more sensitive (13,15,22,35).…”
Section: Discussionmentioning
confidence: 92%
“…In patients who had proliferative disorders, HPV positivity exceeded the percentage of smoking (71.7%), which is considered a major risk factor for oral carcinogenesis (3). Most studies agree that there is no statistically significant correlation between HPV prevalence and smoking history, although it seems that both tobacco and HPV infection may participate in the tumorigenic process in oral mucosa (13,29,34,38,43).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-eight cases were identified and retrospectively reviewed for clinicopathologic features, including patient demographics, sites of tumor origin, and extent of disease, and treatment modalities were extracted from these records. Of these, tissue blocks for molecular analysis were available for 14 cases, and follow-up data for at least 5 years after diagnosis (mean, 3 years) were available for 25 For polymerase chain reaction (PCR), oligonucleotide primers to amplify glyceraldehyde 3-phosphate dehydrogenase (GAPDH), and HPV gene sequences were synthesized commercially (Genosys, The Woodlands, TX). Consensus primers were used to amplify an approximately 450-bp PCR product from an L1 open reading frame of HPVs 6,11,16,18,33.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence has accumulated that some of the oncogenic HPV types are associated with a subset of head and neck cancers, since HPV DNA was found to be present in HNSCC with various morphology and from various sites (oropharynx, oral cavity, larynx, hypopharynx, nasopharynx), with HPV16 DNA strongly predominating over HPV18, 33, and further types (de Villiers et al, 1985;Maitland et al, 1987;Yeudall and Campo, 1991;Rassekh et al, 1998;for review, zur Hausen, 1996). In further studies, a rather frequent coexistence of HPV DNA and p53 mutations was found, and again all sites and histological grades were involved (Barten et al, 1995;Chiba et al, 1996;Scholes et al, 1997;He et al, 1997). This is in strong contrast to the situation in cervical and other anogenital cancers which show an almost complete inverse correlation between HPV and p53 mutations and which share a conspicious undierentiated (basaloid) morpholgy (Schener et al, 1991;Fujita et al, 1992;Crook et al, 1992;Milde-Langosch et al, 1995;zur Hausen, 1996).…”
Section: Introductionmentioning
confidence: 96%